Pharmacokinetics and exposure-safety relationship of ciprofol for sedation in mechanically ventilated patients in the intensive care unit - Lu Liu; Kun Wang; Zhongyi Sun; Pangke Yan; Mengyue Hu; Xiao Liu; Meixia Chen; Nan Wu; Xiaoqiang Xiang (Wiley, 2024)
Abstract Ciprofol (HSK3486) is a newly developed, highly selective γ‐aminobutyric acid‐A (GABAA) receptor potentiator that is recently approved for a new indication of sedation for patients in the intensive care unit (ICU) in China. This analysis aimed to characterize the population pharmacokinetics (PopPKs) of ciprofol and evaluate the relationship of exposure with hypotension in mechanically ventilated patients in the ICU. A total of 462 subjects with 3918 concentration measurements from two clinical trials of mechanically ventilated patients in the ICU, four clinical trials of elective surgical patients, and six clinical trials of healthy subjects were used in the PopPK analysis. Exposure-safety relationship for hypotension was evaluated based on the data gathered from 112 subjects in two clinical trials of mechanically ventilated patients in the ICU. Ciprofol pharmacokinetics (PKs) was adequately described by a three‐compartment linear disposition model with first‐order elimination. Body weight, age, sex, blood sampling site (vein vs. arterial), study design (long‐term infusion vs. short‐term infusion), and patient population (ICU vs. non‐ICU) were identified as statistically significant covariates on the PKs of ciprofol. Within the exposure range of the mechanically ventilated ICU patient population, no meaningful association was observed between ciprofol exposure and the incidence of hypotension. These results support the dosing regimen currently used in mechanically ventilated patients in the ICU.